Role of the Widal test in diagnosing typhoid fever compared with culture at Teaching Al-Hussein Hospital in Nasiriyah - Fatima Rashid Mohan; Amany Shakeir Jaber (Peerian Journals Publishing, 2024)
One of the infectious diseases that affect people is typhoid. Typhoid fever outbreaks, which are mostly caused by Salmonella typhoid and Salmonella paratyphoid A, continue to be a major global health concern. We attempted to demonstrate in our study the value of the Widal test in the typhoid illness diagnosis. Slide agglutination widal test was employed to look at antibiotic susceptibility, culture, and the prevalence of typhoid illness. the study looked on the prevalence of typhoid fever and was carried out at the teaching Al-Hussein hospital between September 2018 and April 2019.the hospital admitted 155 patients who were thought to have typhoid fever. of whom 155 patients received a diagnosis of typhoid fever; the majority of these cases fell between the(>1–16) age range. there were seventy-six (49.03%) females and seventynine (50.96%) males. March and April saw the greatest number of patients, with lower numbers in subsequent months. The Widal test and blood culture were positive in 75 cases (48.38%) of typhoid fever, while the blood culture was positive in 55 cases (35.4%), and 20 cases (17.3%) were negative for the blood culture, but positive for the serological test. Therefore, Widal's test is important in diagnosing typhoid.
Keywords: Widel test; Culture; Typhoid Fever and Hospital